Safety and efficacy of helical tomotherapy following lung-sparing surgery in locally advanced malignant pleural mesothelioma: original article - Layer, Julian; Fischer, Pascal; Dejonckheere, Cas S.; Sarria, Gustavo R.; Mispelbaum, Rebekka; Hattenhauer, Tessa; Wiegreffe, Shari; Glasmacher, Andrea R.; Layer, Katharina; Nour, Youness; Caglayan, Lara; Grau, Franziska; et al. (Strahlentherapie und Onkologie, 2023)
To assess the value of radiation therapy (RT) with helical tomotherapy (HT) in the management of locally advanced malignant pleural mesothelioma (MPM) receiving no or lung-sparing surgery.
Gesehen am 05.03.2024